2006
DOI: 10.1117/12.681775
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the pellicle on final photomask flatness

Abstract: Photomask pellicles play an important role in determining final photomask flatness, which is important to photomask optical performance. This study explores the impact of the pellicle frame flatness and pellicle-to-mask adhesive on photomask flatness. In addition, the change in mask flatness as a function of time after pellicle mounting is studied. Implications of these results on photomask manufacture and photolithography are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Components such as pellicle mounting techniques, pellicle frame height, frame material and adhesive all play an important role in finished photomask flatness. [1][2][3][4][5] In particular, recent studies have shown that adhesive flexibility affect final photomask flatness significantly. 6 This has motivated pellicle suppliers to optimize adhesive properties and to evaluate new adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…Components such as pellicle mounting techniques, pellicle frame height, frame material and adhesive all play an important role in finished photomask flatness. [1][2][3][4][5] In particular, recent studies have shown that adhesive flexibility affect final photomask flatness significantly. 6 This has motivated pellicle suppliers to optimize adhesive properties and to evaluate new adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…During certain conditions crystals formation of haze form on reticle surfaces, the sulfate ion (SO 4 2-) left on the mask surface after SPM (scanning probe microscopes) step is known the most important source cause for the formation of haze defects. And ammonium sulfate has been known to be mostly responsible for haze defects formation on the mask surface, recent investigation reveals that other chemicals such as hydrocarbons, Na, F, Mg, K, Cl or Al are also cause haze defects.…”
mentioning
confidence: 99%